Negative active material, and negative electrode and secondary battery comprising the same
Patent Information
- Application Number
- CN202280012167.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-04
- Filing Date
- 2022-08-09
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-08-09
AI Technical Summary
[0009]韩国专利第10-0794192号涉及一种制造用于锂二次电池的碳涂覆的硅-石墨复合负极活性材料的方法以及制备包含所述负极活性材料的二次电池的方法,但是在解决上述问题方面存在局限
[0020]The negative electrode active material according to an exemplary embodiment of the present invention comprises a surface layer on silicon-containing composite particles, wherein the surface layer contains an amorphous phase that can effectively remove lithium byproducts contained in the silicon-containing composite particles. This is achieved by providing the surface layer as described above on the surface of the silicon-containing composite particles, which, by effectively coating unreacted lithium byproducts, prevents the physical properties of the slurry from deteriorating due to the reaction of lithium byproducts or lithium compounds in the silicon-containing composite particles with moisture in the slurry. Furthermore, because the surface layer has an amorphous phase that promotes the entry and exit of Li ions, it can achieve stable battery capacity, efficiency, resistivity performance, and/or lifespan while effectively reducing side reactions on the slurry.
Smart Images

Figure CN116762189B_ABST
Abstract
Description
Technical Field
[0001] This application claims the priority and benefit of Korean Patent Application No. 10-2021-0107524 filed with the Korean Intellectual Property Office on August 13, 2021 and Korean Patent Application No. 10-2022-0055522 filed with the Korean Intellectual Property Office on May 4, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a negative electrode active material, a negative electrode including the same, and a secondary battery. Background Art
[0003] Recently, with the rapid popularization of battery-powered electronic devices such as mobile phones, notebook computers and electric vehicles, the demand for small, lightweight secondary batteries with relatively high capacity has been increasing sharply. In particular, lithium secondary batteries are lightweight and have high energy density, thus attracting attention as driving power sources for mobile devices. Accordingly, research and development efforts have been actively conducted to improve the performance of lithium secondary batteries.
[0004] Generally, a lithium secondary battery includes a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. Further, for the positive electrode and the negative electrode, active material layers respectively containing a positive electrode active material and a negative electrode active material may be respectively formed on current collectors. Lithium-containing metal oxides such as LiCoO2 and LiMn2O4 are generally used as the positive electrode active material for the positive electrode, and lithium-free carbon-containing active materials and silicon-containing active materials are used as the negative electrode active material for the negative electrode.
[0005] Among negative electrode active materials, silicon-containing active materials have attracted attention because they have higher capacity and excellent high-rate charging characteristics than carbon-containing active materials. However, silicon-containing active materials have the disadvantage that the degree of volume expansion / contraction caused by charging / discharging may be large, and the irreversible capacity may be large, so the initial efficiency may be low.
[0006] On the other hand, among silicon-containing active materials, silicon-containing oxides, specifically SiO x silicon-containing oxide represented by (0<x<2) has the advantage that the degree of volume expansion / contraction caused by charging / discharging can be lower than that of other silicon-containing active materials such as silicon (Si). However, silicon-containing oxides still have the disadvantage that the initial efficiency may be reduced due to the presence of irreversible capacity.
[0007] In this regard, research has been continuously conducted to reduce irreversible capacity and improve initial efficiency by doping or embedding metals such as Li, Al, and Mg into silicon-containing oxides. However, in the case of a negative electrode slurry containing a metal-doped silicon-containing oxide as a negative electrode active material, there may be a problem that metal oxides formed by metal doping react with moisture to increase the pH value of the negative electrode slurry and change its viscosity. That is, there may be problems that the state of the prepared negative electrode may be deteriorated and the charge / discharge efficiency of the negative electrode may be reduced.
[0008] Therefore, there is a need for developing a negative electrode active material that can improve the phase stability of a negative electrode slurry containing a silicon-containing oxide and improve the charge / discharge efficiency of a negative electrode prepared therefrom.
[0009] Korean Patent No. 10-0794192 relates to a method for manufacturing a carbon-coated silicon-graphite composite negative electrode active material for lithium secondary batteries and a method for preparing a secondary battery including the negative electrode active material, but there is a limitation in solving the above problems.
[0010] Related Art Documents
[0011] [Patent Documents]
[0012] (Patent Document 1) Korean Patent No. 10-0794192 Summary of the Invention
[0013] Technical Problem
[0014] The present invention is directed to providing a negative electrode active material, a negative electrode including the same, and a secondary battery.
[0015] Technical Solution
[0016] An exemplary embodiment of the present invention provides a negative electrode active material comprising: SiO x (0<x<2), silicon-containing composite particles including a Li compound; a carbon layer on at least a part of the surface of the silicon-containing composite particles; a surface layer including an amorphous phase on at least a part of the surface of the silicon-containing composite particles; and at least one group 13 element and at least one group 15 element.
[0017] Another exemplary embodiment of the present invention provides a negative electrode including the negative electrode active material.
[0018] Still another exemplary embodiment of the present invention provides a secondary battery including the negative electrode.
[0019] Advantageous Effects of the Invention
[0020] The negative electrode active material according to an exemplary embodiment of the present invention comprises a surface layer on silicon-containing composite particles, wherein the surface layer contains an amorphous phase that can effectively remove lithium byproducts contained in the silicon-containing composite particles. This is achieved by providing the surface layer as described above on the surface of the silicon-containing composite particles, which, by effectively coating unreacted lithium byproducts, prevents the physical properties of the slurry from deteriorating due to the reaction of lithium byproducts or lithium compounds in the silicon-containing composite particles with moisture in the slurry. Furthermore, because the surface layer has an amorphous phase that promotes the entry and exit of Li ions, it can achieve stable battery capacity, efficiency, resistivity performance, and / or lifespan while effectively reducing side reactions on the slurry.
[0021] The negative electrode active material according to an exemplary embodiment of the present invention can have the following effect: because the surface layer contains Li to reduce the Li diffusion resistance on the surface of the negative electrode active material, the discharge rate limiting characteristics (rate performance) become excellent. Attached Figure Description
[0022] The invention will be more fully understood from the following detailed description and accompanying drawings, which are given by way of example only and do not limit the invention.
[0023] Figure 1 An embodiment of the invention is shown, wherein the silicon-containing composite particles have a surface coated with a carbon layer and a surface layer (e.g., a thin film) is coated on the carbon layer.
[0024] Figure 2 An embodiment of the invention is shown, wherein the silicon-containing composite particles have a surface coated with a carbon layer and a surface layer (e.g., an island-like surface layer) is coated on a portion of the carbon layer.
[0025] Figure 3 An embodiment of the invention is shown, wherein the silicon-containing composite particles have partially overlapping and non-overlapping layers of a carbon layer and a surface layer. Detailed Implementation
[0026] This instruction manual will be described in more detail below.
[0027] In this specification, when a part “contains” a constituent element, unless otherwise specifically stated, this does not mean that other constituent elements are excluded, but rather that other constituent elements may also be included.
[0028] In this specification, when a component is arranged "on" other components, this includes not only the case where a component is in contact with other components, but also the case where there are other components between two components.
[0029] Terms or words used in the specification shall not be construed as being limited to typical or dictionary meanings, but shall be construed with meanings and concepts consistent with the technical spirit of the present invention based on the principle that an inventor can properly define the concept of terms to best describe his / her own invention.
[0030] As used in this specification, the singular form of a term includes the plural form unless it has a clear contrary meaning in the context.
[0031] In this specification, the crystallinity of the structure contained in the negative electrode active material can be confirmed by X-ray diffraction analysis, which can be performed using an X-ray diffraction (XRD) analyzer (trade name: D4-endavor, manufacturer: Bruker Corporation), and in addition to said device, devices used in the art can also be appropriately employed.
[0032] In this specification, the presence or absence of elements and the content of elements in the negative electrode active material can be confirmed by ICP analysis, and ICP analysis can be performed using an inductively coupled plasma atomic emission spectrometer (ICPAES, Perkin Elmer 7300).
[0033] In this specification, the average particle diameter (D 50 ) can be defined as the particle diameter corresponding to 50% of the cumulative volume in a particle size distribution curve (the curve in a particle size distribution diagram) of particles. The average particle diameter (D 50 ) can be measured, for example, using a laser diffraction method. The laser diffraction method can generally measure particle sizes from submicron to about several millimeters, and can obtain results with high reproducibility and high resolution.
[0034] Hereinafter, preferred exemplary embodiments of the present invention will be described in detail. However, the exemplary embodiments of the present invention can be modified into various other forms, and the scope of the present invention is not limited to the exemplary embodiments to be described below.
[0035] <Negative Electrode Active Material>
[0036] An exemplary embodiment of the present invention provides a negative electrode active material, the negative electrode active material comprising: silicon-containing composite particles containing SiO x (wherein 0<x<2) and a Li compound; a carbon layer on at least a portion of the surface of the silicon-containing composite particles; a surface layer containing an amorphous phase on at least a portion of the surface of the silicon-containing composite particles; and at least one group 13 element and at least one group 15 element.
[0037] Generally, during the process of doping silicon-containing particles with Li, lithium by-products formed from unreacted lithium are present on the particles, which makes the slurry alkaline when it is formed. Therefore, there are problems that the rheological properties of the slurry change and gas is generated due to the reaction between Si in the silicon-containing particles and the alkali.
[0038] Therefore, in the present invention, by providing a surface layer on the Li-doped silicon-containing composite particles, lithium by-products formed in the Li doping step are effectively removed, and meanwhile, the formed surface layer is formed on the silicon-containing composite particles, thereby functioning to passivate the particles. In this case, since the formed surface layer comprises an amorphous phase that promotes the ingress and egress of Li ions, the effect of effectively reducing side reactions on the slurry and stably achieving the capacity, efficiency, resistance performance and / or lifespan of the battery can be obtained.
[0039] When the surface layer further comprises Li, the Li diffusion resistance on the surface of the negative electrode active material is reduced, so the effect that the discharge rate limiting characteristic (rate performance) becomes excellent is obtained.
[0040] The negative electrode active material according to an exemplary embodiment of the present invention comprises silicon-containing composite particles. The silicon-containing composite particles comprise SiO x (wherein 0<x<2) and a Li compound, and have a carbon layer disposed on at least a part of the surface thereof.
[0041] The SiO x (0<x<2) may correspond to a matrix in the silicon-containing composite particles. The SiO x (0<x<2) may be in a form comprising Si and SiO2, and the Si may also form a phase. That is, x corresponds to the ratio of the amount of Si contained in SiO x (0<x<2) relative to O. When the silicon-containing composite particles comprise SiO x (0<x<2), the discharge capacity of the secondary battery can be improved.
[0042] In an exemplary embodiment of the present invention, the silicon-containing composite particles may comprise a Li compound.
[0043] The Li compound may correspond to a dopant in the silicon-containing composite particles. The Li compound may exist in the silicon-containing composite particles in at least one form selected from lithium atoms, lithium silicates, lithium silicides and lithium oxides. When the silicon-containing composite particles comprise the Li compound, the effect of improving the initial efficiency is obtained.
[0044] The Li compound is in a form where the silicon-containing composite particles are doped with the compound, and may be distributed on the surface and / or inside the silicon-containing composite particles. Since the Li compound is distributed on the surface and / or inside the silicon-containing composite particles, the volume expansion / contraction of the silicon-containing composite particles can be controlled to an appropriate level, and the effect of preventing damage to the active material can be achieved. In addition, the Li compound may be contained in terms of reducing the proportion of irreversible phases (such as SiO₂) in the silicon-containing oxide particles to improve the efficiency of the active material.
[0045] In an exemplary embodiment of the present invention, the Li compound may exist in the form of lithium silicate. The lithium silicate is represented by Li a Si b O c (2≤a≤4, 0<b≤2, 2≤c≤5) and can be classified into crystalline lithium silicate and amorphous lithium silicate. The crystalline lithium silicate may exist in the silicon-containing particles in the form of at least one lithium silicate selected from the group consisting of Li₂SiO₃, Li₄SiO₄ and Li₂Si₂O₅, and the amorphous lithium silicate may comprise Li a Si b O c (2≤a≤4, 0<b≤2, 2≤c≤5) in a complex structure, and is not limited to said form.
[0046] In an exemplary embodiment of the present invention, when X-ray diffraction analysis is performed on the negative electrode active material, a peak derived from Si may appear, and a peak derived from at least one of Li₂SiO₃ and Li₂Si₂O₅ may appear.
[0047] The peak derived from Si may include diffraction peaks caused by Si(111) and / or Si(220), the diffraction peak caused by Si(111) may appear in the range of diffraction angle (2θ) = 27.5° to 29.5°, and the diffraction peak caused by Si(220) may appear in the range of diffraction angle (2θ) = 45° to 50°.
[0048] The peak derived from Li₂SiO₃ may appear in the range of diffraction angle (2θ) = 17.5° to 20.5°, and the peak derived from Li₂Si₂O₅ may appear in the range of diffraction angle (2θ) = 23.0° to 25.5°. However, the peak derived from said compound may include peaks appearing in other diffraction angle ranges outside the above diffraction angle range.
[0049] X-ray diffraction analysis of the negative electrode active material can be performed using an X-ray diffraction (XRD) analyzer (trade name: D4-endavor, manufacturer: Bruker). Specifically, the sample for XRD analysis is prepared by placing 0.3 g of the negative electrode active material in a cylindrical holder with a diameter of 2.5 cm and a height of 2.5 mm and flattening it with a glass slide to keep the height of the sample in the holder constant. Then, the peaks can be measured by setting the XRD analyzer's scan time to 1 hour and 15 minutes, the measurement area to a region with 2θ ranging from 10° to 90°, and setting the step time and step size to scan 2θ 0.02° per second.
[0050] In an exemplary embodiment of the present invention, the Li content can be from 0.1 parts by weight to 25 parts by weight based on a total of 100 parts by weight of the negative electrode active material. Specifically, the Li content can be from 1 part by weight to 15 parts by weight, and more specifically from 2 parts by weight to 11 parts by weight. In one example, the Li content can be 4 parts by weight or more, 6 parts by weight or more, 8 parts by weight or more, and can be less than 10 parts by weight based on a total of 100 parts by weight of the negative electrode active material. The problem is that as the Li content increases, the initial efficiency increases, but the discharge capacity decreases. Therefore, when the content meets the above-mentioned range of 0.1 parts by weight to 25 parts by weight, an appropriate discharge capacity and initial efficiency can be achieved.
[0051] The Li element content can be confirmed by ICP analysis. Specifically, after a predetermined amount (approximately 0.01 g) of the negative electrode active material is aliquoted, the aliquot is transferred to a platinum crucible and nitric acid, hydrofluoric acid, or sulfuric acid is added to completely decompose the negative electrode active material on a hot plate. Then, an inductively coupled plasma atomic emission spectrometer (ICPAES, Perkin-Elmer 7300) is used to measure the intensity of a standard solution (5 mg / kg) at the intrinsic wavelength of the element to be analyzed, creating a reference calibration curve. Subsequently, pretreated sample solutions and blank samples are introduced into the instrument separately, and the actual intensity is calculated by measuring their respective intensities. The concentration of each component is calculated relative to the created calibration curve, and the elemental content of the prepared negative electrode active material can then be analyzed by converting the sum to a theoretical value.
[0052] In an exemplary embodiment of the present invention, the silicon-containing composite particles may contain additional metal atoms. The metal atoms may exist in the silicon-containing composite particles in at least one form selected from metal atoms, metal silicates, metal silicides, and metal oxides. The metal atoms may contain at least one selected from the group consisting of Mg, Li, Al, and Ca. This can improve the initial efficiency of the negative electrode active material.
[0053] The silicon-containing composite particles according to an exemplary embodiment of the present invention have a carbon layer disposed on at least a portion of their surface. In this case, the carbon layer may be in the form of being coated on at least a portion of the particle surface. That is, the carbon layer may be in the form of being partially coated on the particle surface or coated on the entire particle surface. Through the carbon layer, conductivity is imparted to the negative electrode active material, and the initial efficiency, lifetime characteristics, and battery capacity characteristics of the secondary battery can be improved.
[0054] In an exemplary embodiment of the present invention, the carbon layer comprises an amorphous phase.
[0055] Specifically, the carbon layer may comprise amorphous carbon. Alternatively, the carbon layer may be an amorphous carbon layer. The amorphous carbon can suppress the expansion of the silicon-containing composite particles by appropriately maintaining the strength of the carbon layer.
[0056] Furthermore, the carbon layer may or may not contain additional crystalline carbon.
[0057] The crystalline carbon can further improve the conductivity of the negative electrode active material. The crystalline carbon may contain at least one selected from the group consisting of fullerenes, carbon nanotubes, and graphene.
[0058] The amorphous carbon can suppress the expansion of the silicon-containing composite particles by appropriately maintaining the strength of the carbon layer. The amorphous carbon can be a carbide selected from at least one of the group consisting of tar, pitch, and other organic materials, or it can be a carbon-containing material formed using hydrocarbons as a source in chemical vapor deposition.
[0059] The other organic materials may be carbonides of sucrose, glucose, galactose, fructose, lactose, mannose, ribose, aldose, or ketose, as well as carbonides of organic materials selected from combinations thereof.
[0060] The hydrocarbon can be a substituted or unsubstituted aliphatic or alicyclic hydrocarbon, or a substituted or unsubstituted aromatic hydrocarbon. The substituted or unsubstituted aliphatic or alicyclic hydrocarbons can be methane, ethane, ethylene, acetylene, propane, butane, butene, pentane, isobutane, hexane, etc. Examples of the substituted or unsubstituted aromatic hydrocarbons include benzene, toluene, xylene, styrene, ethylbenzene, diphenylmethane, naphthalene, phenol, cresol, nitrobenzene, chlorobenzene, indene, coumarone, pyridine, anthracene, phenanthrene, etc.
[0061] In an exemplary embodiment of the present invention, based on 100 parts by weight of the anode active material in total, the content of the carbon layer may be 0.1 part by weight to 50 parts by weight, 0.1 part by weight to 30 parts by weight, or 0.1 part by weight to 20 parts by weight. More specifically, the content of the carbon layer may be 0.5 part by weight to 15 parts by weight, 1 part by weight to 10 parts by weight, 2 parts by weight to 8 parts by weight, or 3 parts by weight to 5 parts by weight. When the above range of 0.1 part by weight to 50 parts by weight is satisfied, a decrease in the capacity and efficiency of the anode active material can be prevented.
[0062] In an exemplary embodiment of the present invention, the thickness of the carbon layer may be 1 nm to 500 nm, and specifically 5 nm to 300 nm. When the above range of 1 nm to 500 nm is satisfied, the electrical conductivity of the anode active material can be improved, the volume change of the anode active material can be easily suppressed, and side reactions between the electrolyte and the anode active material can be inhibited, thereby achieving the effect of improving the initial efficiency and / or service life of the battery.
[0063] Specifically, the carbon layer may be formed by chemical vapor deposition (CVD) using at least one hydrocarbon gas selected from the group consisting of methane, ethane and acetylene.
[0064] The silicon-containing composite particles according to an exemplary embodiment of the present invention comprise a surface layer provided on at least a portion of the silicon-containing composite particles.
[0065] The surface layer may be in a form coated on at least a portion of the silicon-containing composite particles having the carbon layer provided on the surface thereof. That is, the surface layer may be in a form partially coated on the particle surface or coated on the entire particle surface. Examples of the shape of the surface layer include island-type, thin film-type, etc., but the shape of the surface layer is not limited thereto.
[0066] The surface layer may be provided on at least a portion of the outer surface of the carbon layer. That is, the surface layer is adjacently coated on the carbon layer, thereby can be comprised of SiO x (0<x<2) and a Li compound in the form of particle-carbon layer-surface layer. The surface layer may substantially or completely cover the carbon layer, or may partially cover the carbon layer.
[0067] As shown in Figure 1 , the carbon layer 2 is present on the surface of the silicon-containing composite particle 1 and the surface layer is present on the entire surface of the carbon layer 2. Figure 1 indicates that the surface layer is a thin film layer.
[0068] As shown in Figure 2 , the carbon layer 2 is present on the surface of the silicon-containing composite particle 1 and the surface layer is present on a part of the surface of the carbon layer 2. Figure 2 indicating that the surface layer has an island shape.
[0069] The surface layer may be disposed on a region where no carbon layer is provided x (0<x<2) and Li compound on the particle surface. That is, the surface layer is adjacently coated on the particles comprising SiO x (0<x<2) and a Li compound, whereby it can be provided in a form of particles comprising SiO x (0<x<2) and a Li compound - the surface layer. As shown in Figure 3 , the carbon layer 2 and the surface layer 3 are present on overlapping portions and non-overlapping portions of the surface of the silicon-containing composite particle 1.
[0070] In an exemplary embodiment of the present invention, the negative electrode active material comprises at least one Group 13 element and at least one Group 15 element. Exemplary Group 13 elements include B, Al, Ga, In and Tl. Exemplary Group 15 elements include N, P, As, Sb and Bi.
[0071] In an exemplary embodiment of the present invention, the negative electrode active material comprises Al and P.
[0072] In an exemplary embodiment of the present invention, the negative electrode active material comprises B and P.
[0073] In an exemplary embodiment of the present invention, the negative electrode active material comprises Li, at least one Group 13 element and at least one Group 15 element.
[0074] In an exemplary embodiment of the present invention, the negative electrode active material comprises Li, Al and P.
[0075] In an exemplary embodiment of the present invention, the negative electrode active material comprises Li, B and P.
[0076] In an exemplary embodiment of the present invention, Li, the Group 13 element and the Group 15 element can be detected in ICP analysis of the negative electrode active material. Specifically, the Group 13 element may be Al or B, and the Group 15 element may be P.
[0077] In an exemplary embodiment of the present invention, the surface layer may comprise Al and P.
[0078] In an exemplary embodiment of the present invention, the surface layer may comprise B and P.
[0079] In an exemplary embodiment of the present invention, the surface layer may comprise Al, P and O elements.
[0080] In an exemplary embodiment of the present invention, the surface layer may comprise B, P and O elements.
[0081] In an exemplary embodiment of the present invention, the surface layer may comprise Li, Al, P and O elements.
[0082] In an exemplary embodiment of the present invention, the surface layer may comprise Li, B, P and O elements.
[0083] In an exemplary embodiment of the present invention, based on 100 parts by weight of the total negative electrode active material, the content of the at least one group 13 element may be 0.05 parts by weight to 0.3 parts by weight. Specifically, the content of the at least one group 13 element may be 0.1 parts by weight to 0.4 parts by weight, 0.12 parts by weight to 0.35 parts by weight, or 0.15 parts by weight to 0.3 parts by weight.
[0084] In an exemplary embodiment of the present invention, based on 100 parts by weight of the total negative electrode active material, the content of the at least one group 15 element may be 0.05 parts by weight to 2 parts by weight. Specifically, the content of the at least one group 15 element may be 0.1 parts by weight to 1.5 parts by weight, or 0.15 parts by weight to 1 part by weight.
[0085] The surface layer may comprise Al z P w O v (0<z≤10, 0<w≤10 and 0<v≤10) phase. The Al z P w O v phase may comprise aluminum oxide, phosphorus oxide, aluminum phosphate, etc., and z, w and v represent the atomic ratio of each atom. In an example, the Al z P w O v phase may comprise a mixture or compound formed of AlPO4, Al(PO3)3, etc., but is not limited thereto.
[0086] The surface layer may comprise Li y Al z P w O v (0<y≤10, 0<z≤10, 0<w≤10 and 0<v≤10) phase. The Li y Al z P w O v phase may comprise aluminum oxide, phosphorus oxide, lithium oxide, aluminum phosphate, lithium salt, lithium phosphate, lithium aluminate, etc., and y, z, w and v represent the atomic ratio of each atom. In an example, Li y Al z Pw O v The phase may include, but is not limited to, mixtures or compounds formed from Li3PO4, AlPO4, Al(PO3)3, LiAlO2, etc.
[0087] The surface layer may comprise B z1 P w1 O v1 (0<z1≤10, 0<w1≤10 and 0<v1≤10) phase. The B z1 P w1 O v1 The phase may include boron oxide, phosphorus oxide, borophosphate, etc., and z1, w1 and v1 represent the atomic ratio of each atom.
[0088] The surface layer may comprise Li y1 B z1 P w1 O v1 (0<y1≤10, 0<z1≤10, 0<w1≤10 and 0<v1≤10) phase. The Li y1 B z1 P w1 O v1 The phase may include boron oxide, phosphorus oxide, lithium oxide, borophosphate, lithium salt, lithium phosphate, lithium borate, etc., and y1, z1, w1 and v1 represent the atomic ratio of each atom.
[0089] When an inorganic surface layer comprising the above-mentioned phase is provided, the phenomenon that the viscosity of the slurry is reduced due to the reaction between the Li compound contained in the silicon-containing composite particles and the moisture in the slurry can be prevented, and the effect of improving the stability of the electrode state and / or the charge / discharge capacity can be achieved.
[0090] In an exemplary embodiment of the present invention, the surface layer may comprise an amorphous phase.
[0091] In an exemplary embodiment of the present invention, the surface layer may be an amorphous phase.
[0092] The surface layer may comprise Al z P w O v (0<z≤10, 0<w≤10 and 0<v≤10) phase, and the Al z P w O v (0<z≤10, 0<w≤10 and 0<v≤10) phase may be an amorphous phase.
[0093] The surface layer may comprise Li y Al z P w Ov (0<y≤10, 0<z≤10, 0<w≤10 and 0<v≤10) phase, and said Li y Al z P w O v (0<y≤10, 0<z≤10, 0<w≤10 and 0<v≤10) phase may be an amorphous phase.
[0094] When the surface layer is made of a crystalline material, it may become difficult for Li ions to enter and exit, so there may be a problem of deterioration in resistance and lifespan characteristics. Compared with the case where the surface layer does not contain an amorphous phase, the negative electrode active material of the present invention, since the surface layer contains the above amorphous phase to promote the entry and exit of Li ions, can have the effect of stably achieving capacity and / or efficiency while effectively reducing side reactions on the slurry.
[0095] In an exemplary embodiment of the present invention, the surface layer may further comprise one or more selected from the group consisting of Li₂O, LiOH and Li₂CO₃. Generally, since residual materials during the doping of silicon-containing particles with lithium may be exposed to moisture or air to form lithium by-products such as Li₂O, LiOH and Li₂CO₃, the surface layer may be in a form comprising one or more selected from the group consisting of Li₂O, LiOH and Li₂CO₃.
[0096] In an exemplary embodiment of the present invention, y may satisfy 0<y≤3.
[0097] In an exemplary embodiment of the present invention, z may satisfy 0<z≤1.
[0098] In an exemplary embodiment of the present invention, w may satisfy 0.5≤w≤3.
[0099] In an exemplary embodiment of the present invention, v may satisfy 4<v≤12.
[0100] The surface layer may be formed by dry-mixing i) silicon-containing composite particles and aluminum phosphate, ii) silicon-containing composite particles, an aluminum precursor and a phosphorus precursor, or iii) silicon-containing composite particles and a Li-Al-P-O-containing precursor, and then heat-treating the mixture, or formed by mixing i), ii) or iii) with a solvent, and then allowing the mixture to react while evaporating the solvent.
[0101] In an exemplary embodiment of the present invention, when X-ray diffraction analysis is performed on the negative electrode active material, no crystalline peak derived from the surface layer appears. Specifically, no peak derived from Li contained in the surface layer is detected y Al z P w O vcrystallization peak of a phase where 0 < y ≤ 10, 0 < z ≤ 10, 0 < w ≤ 10 and 0 < v ≤ 10. When a crystallization peak derived from the surface layer appears, there may be a problem of capacity and / or efficiency degradation caused by the surface layer containing an excessive amount of crystalline material. In an example, the crystallization peak derived from the surface layer can be identified by the change before and after coating the surface layer. Specifically, in the case of XRD, a crystallization peak is detected, and it can be confirmed that when there is no difference in the XRD pattern of the negative electrode active material before and after coating the surface layer, no crystallization peak derived from the surface layer appears and the surface layer is formed of an amorphous phase.
[0102] In an exemplary embodiment of the present invention, based on 100 parts by weight of the surface layer in total, the content of the amorphous phase contained in the surface layer may be more than 50 parts by weight. Specifically, based on 100 parts by weight of the surface layer in total, the content of the amorphous phase may be 60 parts by weight or more, 70 parts by weight or more, 80 parts by weight or more, 90 parts by weight or more, 95 parts by weight or more, or 99 parts by weight or more, and may be 100 parts by weight or less or less than 100 parts by weight. By satisfying the above range of more than 50 parts by weight, the effect of effectively suppressing side reactions on the slurry and stably achieving capacity and / or efficiency can be obtained.
[0103] In an exemplary embodiment of the present invention, based on 100 parts by weight of the negative electrode active material in total, the content of the surface layer may be 10 parts by weight or less. Specifically, the content of the surface layer may be 8 parts by weight or less, 6 parts by weight or less, or 5 parts by weight or less, and may be 0.1 part by weight or more or 0.5 part by weight or more. More specifically, the content of the surface layer may be 1 part by weight or more and 5 parts by weight or less, or 1.5 parts by weight or more and 3 parts by weight or less. There is a problem that when the content of the surface layer is lower than the above range (for example, lower than 0.1 part by weight), it may be difficult to prevent gas generation on the slurry, and when the content is higher than the above range (for example, higher than 10 parts by weight), it may be difficult to achieve capacity or efficiency.
[0104] In an exemplary embodiment of the present invention, the weight ratio of the surface layer to the carbon layer may be 1:0.1 to 1:30. Specifically, the weight ratio may be 1:0.5 to 1:5, or 1:1 to 1:4, or 1:1 to 1:3. By satisfying the above range of 1:0.1 to 1:30, the silicon-containing composite particles can be effectively coated with the carbon layer and the surface layer, thereby efficiently suppressing side reactions on the slurry and stably achieving capacity and / or efficiency. Conversely, there may be a problem that when the content of the surface layer is much higher than the content of the carbon layer, it may be difficult to achieve capacity or efficiency, and when the content of the carbon layer is much higher than the content of the surface layer, it may be difficult to prevent gas generation on the slurry.
[0105] In an exemplary embodiment of the present invention, the content of the surface layer may be 90 parts by weight or less based on 100 parts by weight of the carbon layer. Specifically, the content of the surface layer may be 80 parts by weight or less, 70 parts by weight or less, 60 parts by weight or less, or 50 parts by weight or less based on 100 parts by weight of the carbon layer. Furthermore, the content of the surface layer may be 0.1 parts by weight or more, 1 part by weight or more, 5 parts by weight or more, or 10 parts by weight or more based on 100 parts by weight. By satisfying the above ranges, it is possible to effectively coat the silicon-containing composite particles with the carbon layer and the surface layer to effectively suppress side reactions on the slurry and stably achieve capacity and / or efficiency.
[0106] The average particle size (D) of the negative electrode active material 50 The particle size can range from 0.1 μm to 30 μm, specifically from 1 μm to 20 μm, and more specifically from 1 μm to 10 μm. When the above range of 0.1 μm to 30 μm is met, the active material can be structurally stable during charging and discharging, and the problem of excessive volume expansion / contraction levels with an excessively large increase in average particle size can be prevented, as well as the problem of reduced initial efficiency due to excessively small average particle size can be prevented.
[0107] <Preparation Methods of Negative Electrode Active Materials>
[0108] In an exemplary embodiment of the present invention, a method for preparing a negative electrode active material includes: preparing silicon-containing composite particles; and forming a surface layer on at least a portion of the silicon-containing composite particles.
[0109] The silicon-containing composite particles can be formed by heating and vaporizing Si powder and SiO2 powder under vacuum, and then depositing the vaporized mixed gas to form pre-particles; forming a carbon layer on the pre-particles; and mixing the pre-particles with the carbon layer thereon with Li powder, and then heat-treating the resulting mixture.
[0110] Alternatively, the silicon-containing composite particles can be formed by heating and vaporizing Si powder and SiO2 powder under vacuum, and then depositing the vaporized mixed gas to form pre-particles; and mixing the pre-particles with Li powder, and then heat-treating the resulting mixture.
[0111] Specifically, the mixture of Si powder and SiO2 powder can be heat-treated under vacuum at 1400°C to 1800°C or 1400°C to 1600°C.
[0112] The preparatory particles formed can be SiO x It exists in the form (x=1).
[0113] The silicon-containing composite particles may comprise the above-mentioned Li silicate, Li silicide, Li oxide, etc.
[0114] The particle size of the silicon-containing composite particles can be adjusted by methods such as ball milling, jet milling or air classification, and the method is not limited thereto.
[0115] In the formation of the carbon layer, the carbon layer can be prepared by a chemical vapor deposition (CVD) method using a hydrocarbon gas or by carbonizing a material used as a carbon source.
[0116] Specifically, the carbon layer can be formed by introducing the prepared precursor particles into a reaction furnace, and then subjecting the hydrocarbon gas to chemical vapor deposition (CVD) at 600°C to 1,200°C. The hydrocarbon gas may be at least one hydrocarbon gas selected from the group consisting of methane, ethane, propane and acetylene, and the heat treatment may be performed at 900°C to 1,000°C.
[0117] In an exemplary embodiment of the present invention, disposing a surface layer on at least a portion of the silicon-containing composite particle may comprise mixing the silicon-containing composite particle with a precursor containing a Group 13 element and a Group 15 element and allowing the mixture to react.
[0118] The Group 13 element may be Al or B.
[0119] The Group 15 element may be P.
[0120] The precursor comprising the Group 13 element and the Group 15 element may be aluminum phosphate or boron phosphate.
[0121] Disposing a surface layer on at least a portion of the silicon-containing composite particles may comprise: dry-mixing the silicon-containing composite particles and aluminum phosphate and subjecting the resulting mixture to heat treatment, or mixing the silicon-containing composite particles and aluminum phosphate with a solvent, and then subjecting the resulting mixture to heat treatment, so that the silicon-containing composite particles react with aluminum phosphate while the solvent is evaporated. When the surface layer is formed by said method, the surface layer can be easily formed by the reaction of Li by-products formed during the preparation of the silicon-containing composite particles with aluminum phosphate.
[0122] The aluminum phosphate may be Al b P c O d in the form of (0<b≤10, 0<c≤10 and 0<d≤10). Specifically, the aluminum phosphate may be Al(PO3)3 or AlPO4, which is not limited thereto, and salts used for forming a surface layer in the art may be appropriately employed.
[0123] The boron phosphate may be B b1 Pc1 O d1 in the form of (0 < b1 ≤ 10, 0 < c1 ≤ 10 and 0 < d1 ≤ 10).
[0124] In another exemplary embodiment of the present invention, providing a surface layer on at least a part of the silicon-containing composite particles may include mixing and reacting the silicon-containing composite particles, a precursor containing a Group 13 element, and a precursor containing a Group 15 element.
[0125] The precursor containing a Group 15 element may be a phosphorus precursor.
[0126] Specifically, providing a surface layer on at least a part of the silicon-containing composite particles may include: dry-mixing the silicon-containing composite particles, the precursor containing a Group 13 element and the phosphorus precursor and subjecting the resulting mixture to heat treatment, or mixing the silicon-containing composite particles, the precursor containing a Group 13 element and the phosphorus precursor with a solvent, then subjecting the resulting mixture to heat treatment to evaporate the solvent while reacting the silicon-containing composite particles, the precursor containing a Group 13 element and the phosphorus precursor. When the surface layer is formed by said method, the surface layer can be easily formed through the reaction between the Li by-product formed during the preparation of the silicon-containing composite particles and the precursor containing a Group 13 element and the phosphorus precursor.
[0127] The precursor containing a Group 13 element may be an aluminum precursor or a boron precursor.
[0128] The aluminum precursor may be Al a O b aluminum oxide in the form of (0 < a ≤ 10, 0 < b ≤ 10), specifically Al2O3.
[0129] Alternatively, the aluminum precursor may be aluminum hydroxide, aluminum nitrate, aluminum sulfate, etc., specifically Al(OH)3, Al(NO3)3·9H2O or Al2(SO4)3, and is not limited thereto; aluminum precursors used in the art for forming a surface layer may be appropriately employed.
[0130] The boron precursor may be B(OH)3, (BOH)3O3 or H2B4O7, etc., but is not limited thereto, and boron precursors used in the art for forming a surface layer may be appropriately employed.
[0131] The phosphorus precursor may be P c O d phosphorus oxide in the form of (0 < c ≤ 10, 0 < d ≤ 10).
[0132] Alternatively, the phosphorus precursor may be ammonium phosphate, diammonium hydrogen phosphate, phosphoric acid, etc., specifically (NH4)3PO4, (NH4)2HPO4, H3PO4 or NH4H2PO4, but is not limited thereto, and phosphorus precursors used in the art for forming a surface layer may be appropriately selected.
[0133] Alternatively, providing a surface layer on at least a portion of the silicon-containing composite particles may comprise: dry-mixing the silicon-containing composite particles and the Li-Al-P-O-containing precursor and heat-treating the resulting mixture; or mixing the silicon-containing composite particles and the Li-Al-P-O-containing precursor with a solvent, and then heat-treating the resulting mixture to allow the silicon-containing composite particles to react with the Li-Al-P-O-containing precursor while evaporating the solvent. When the surface layer is formed by this method, the surface layer can be formed by directly introducing the Li-Al-P-O-containing precursor.
[0134] The Li-Al-P-O-containing precursor may be in the form of Li y Al z P w O v (0<y≤10, 0<z≤10, 0<w≤10 and 0<v≤10). Specifically, the above-mentioned Li-Al-P-O-containing precursor may be a mixture or a compound formed by compounding Li3PO4, AlPO4, Al(PO3)3, LiAlO2, etc., but is not limited thereto, and structures used in the art for forming a surface layer may be appropriately selected.
[0135] When providing a surface layer on at least a portion of the silicon-containing composite particles, the heat treatment may be performed at 500°C to 700°C, specifically 550°C to 650°C. However, the heat treatment temperature is not limited thereto and may vary depending on the salts, precursors, etc. used. When the heat treatment temperature is higher than the above range of 500°C to 700°C, the surface layer is formed of a crystalline material, which may make it difficult for Li ions to pass in and out through the surface layer, thus there may be problems of deterioration in resistance and cycle life characteristics as well as deterioration in capacity and / or efficiency. When the heat treatment temperature satisfies the above range of 500°C to 700°C, the salt or precursor can react well with Li by-products, so that the surface layer contains Li, the durability of the formed negative electrode active material against moisture is enhanced, and the Li diffusion resistance on the surface of the negative electrode active material is reduced, therefore it has the effect of making the rate capability excellent.
[0136] The solvent may be water or ethanol and is not limited thereto, and solvents used in the art may be appropriately selected.
[0137] The surface layer formed on the silicon-containing composite particles preferably comprises Li y Al z P w Ov (0 < y ≤ 10, 0 < z ≤ 10, 0 < w ≤ 10 and 0 < v ≤ 10) phase, and the Li y Al z P w O v phase may be an amorphous phase.
[0138] The content regarding the surface layer is the same as described above.
[0139] <Negative Electrode>
[0140] The negative electrode according to the exemplary embodiment of the present invention may comprise the above negative electrode active material.
[0141] Specifically, the negative electrode may comprise a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode active material layer may comprise the above negative electrode active material. In addition, the negative electrode active material layer may further comprise a binder and / or a conductive material.
[0142] The negative electrode active material layer may be formed by the following method: applying a negative electrode slurry comprising the negative electrode active material, the binder and / or the conductive material onto at least one surface of the negative electrode current collector, and drying and calendering the negative electrode slurry applied onto the negative electrode current collector.
[0143] The negative electrode slurry may comprise the above negative electrode active material, the binder and / or the conductive material.
[0144] The negative electrode slurry may further comprise an additional negative electrode active material.
[0145] As the additional negative electrode active material, compounds capable of reversibly intercalating and deintercalating lithium may be used. Specific examples thereof include: carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fibers and amorphous carbon; metal compounds capable of forming alloys with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys or Al alloys; metal oxides capable of being doped and undoped with lithium such as SiO β(0<β<2), SnO2, vanadium oxide, lithium titanium oxide, and lithium vanadium oxide; or composites comprising the aforementioned metal compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more thereof may be used. Furthermore, a thin film of metallic lithium may be used as the negative electrode active material. Alternatively, both low-crystallinity carbon and high-crystallinity carbon may be used as carbon materials. Typical examples of low-crystallinity carbon include soft carbon and hard carbon, and typical examples of high-crystallinity carbon include irregular, plate-like, flake-like, spherical, or fibrous natural or artificial graphite, floating graphite, pyrolytic carbon, mesophase pitch-like carbon fibers, mesophase carbon microspheres, mesophase pitch, and high-temperature sintered carbon such as coke derived from petroleum or coal tar pitch.
[0146] The additional negative electrode active material may be a carbon-containing negative electrode active material.
[0147] In an exemplary embodiment of the present invention, the weight ratio of the above-mentioned negative electrode active material contained in the negative electrode slurry to the other negative electrode active material can be 10:90 to 90:10, specifically 10:90 to 50:50.
[0148] The negative electrode current collector only needs to be conductive without causing chemical changes to the battery, and there are no particular limitations. For example, as a current collector, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel with a surface treatment of carbon, nickel, titanium, silver, etc. can be used. Specifically, transition metals that adsorb carbon well, such as copper or nickel, can be used as current collectors. Although the thickness of the current collector can be from 6 μm to 20 μm, the thickness of the current collector is not limited to this.
[0149] The adhesive may contain at least one selected from the group consisting of: polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, polyacrylic acid, and materials whose hydrogen is replaced by Li, Na, Ca, etc., and may also contain various copolymers thereof.
[0150] There are no particular limitations on the conductive material, as long as it is conductive and will not cause chemical changes to the battery. For example, the following can be used: graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal cracking black; conductive fibers such as carbon fiber or metal fiber; conductive tubes such as carbon nanotubes; fluorocarbon powders; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives, etc.
[0151] The negative electrode slurry may further include a solvent for forming the negative electrode slurry. Specifically, the solvent for forming the negative electrode slurry may include at least one selected from the group consisting of distilled water, ethanol, methanol, and isopropanol, and more specifically, distilled water may be used to promote the dispersion of the components.
[0152] In an exemplary embodiment of the present invention, based on a total of 100 parts by weight of the negative electrode slurry, the weight of the solid component of the negative electrode slurry can be from 20 parts by weight to 75 parts by weight, specifically from 30 parts by weight to 70 parts by weight.
[0153] Secondary batteries
[0154] A secondary battery according to an exemplary embodiment of the present invention may include the negative electrode described above according to the exemplary embodiment. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator inserted between the positive and negative electrodes, and an electrolyte, and the negative electrode is the same as the negative electrode described above. Since the negative electrode has already been described, its specific description will be omitted.
[0155] The positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on at least one surface of the positive electrode current collector and containing positive electrode active material.
[0156] In the positive electrode, there are no particular limitations on the positive electrode current collector, as long as it is conductive and will not cause chemical changes to the battery. For example, materials such as stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel with a surface treated with carbon, nickel, titanium, silver, etc., can be used. Furthermore, the positive electrode current collector can typically have a thickness of 3μm to 500μm, and forming fine irregularities on the surface of the current collector can enhance the adhesion of the positive electrode active material. For example, the positive electrode current collector can be used in various forms such as films, sheets, foils, meshes, porous bodies, foams, and nonwoven fabrics.
[0157] The positive electrode active material can be a commonly used positive electrode active material. Specifically, the positive electrode active material includes: layered compounds such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2) or compounds replaced by one or more transition metals; lithium iron oxide such as LiFe3O4; lithium manganese oxide such as Li 1+c1 Mn 2-c1 O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5 and Cu2V2O7; chemical formula LiNi 1-c2 M c2 O2 (where M is at least one selected from the group consisting of: Co, Mn, Al, Cu, Fe, Mg, B, and Ga, and c2 satisfies 0.01 ≤ c2 ≤ 0.3) represents a Ni-site type lithium nickel oxide; chemical formula LiMn 2-c3 M c3 Lithium-manganese composite oxides represented by O2 (where M is selected from at least one of the following groups: Co, Ni, Fe, Cr, Zn, and Ta, and c3 satisfies 0.01 ≤ c3 ≤ 0.1) or Li2Mn3MO8 (where M is selected from at least one of the following groups: Fe, Co, Ni, Cu, and Zn); LiMn2O4 with Li partially replaced by alkaline earth metal ions, etc., but not limited to these. The positive electrode can be Li metal.
[0158] The positive electrode active material layer may include, in addition to the above-mentioned positive electrode active material, a positive electrode conductive material and a positive electrode binder.
[0159] In this context, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without particular restriction as long as the positive electrode conductive material is electronically conductive without causing chemical changes in the constructed battery. Specific examples include: graphite such as natural or artificial graphite; carbon-containing materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal cracking black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and any one or a mixture of two or more thereof can be used.
[0160] The positive electrode adhesive is used to improve the bonding between positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode current collector. Specific examples may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and any one or a mixture of two or more thereof may be used.
[0161] The separator separates the negative and positive electrodes and provides a path for lithium ions to move. It can be used without particular limitations, as long as it is typically used in secondary batteries. In particular, separators with excellent electrolyte retention and low resistance to electrolyte ion migration are preferred. Specifically, porous polymer membranes can be used, such as those formed from polyolefin polymers like ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers; or laminates of two or more layers thereof. Additionally, typical porous nonwoven fabrics can be used, such as nonwoven fabrics made from high-melting-point glass fibers or polyethylene terephthalate fibers. Furthermore, coated separators containing ceramic components or polymer materials can be used to ensure heat resistance or mechanical strength, and can be selectively used as single-layer or multi-layer structures.
[0162] Examples of the electrolytes include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the preparation of lithium secondary batteries.
[0163] Specifically, the electrolyte may contain a non-aqueous organic solvent and a metal salt.
[0164] As the aforementioned non-aqueous organic solvent, aprotic organic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butyl carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triphosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolium ketone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate can be used.
[0165] In particular, among the carbonate organic solvents, ethylene carbonate and propylene carbonate, as cyclic carbonates, have high dielectric constants as high-viscosity organic solvents, thereby effectively dissociating lithium salts. Therefore, the cyclic carbonates are preferred to be used. Furthermore, such cyclic carbonates can be mixed in appropriate proportions with low-viscosity and low-dielectric-constant linear carbonates such as dimethyl carbonate and diethyl carbonate to prepare electrolytes with high conductivity. Therefore, the cyclic carbonates are even more preferred to be used.
[0166] As the metal salt, a lithium salt can be used, which is a material readily soluble in non-aqueous electrolytes. For example, as the anion of the lithium salt, one or more selected from the group consisting of: F - Cl - I - NO3 - N(CN)2 - BF4 - ClO4 - PF6 - (CF3)2PF4 - (CF3)3PF3 - (CF3)4PF2 - (CF3)5PF - (CF3)6P - CF3SO3 - CF3CF2SO3 - (CF3SO2)2N - (FSO2)2N - CF3CF2(CF3)2CO - (CF3SO2)2CH - (SF5)3C - (CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - CH3CO2 - SCN - and (CF3CF2SO2)2N - .
[0167] In the electrolyte, in order to improve battery life characteristics, suppress battery capacity reduction, and improve battery discharge capacity, in addition to the above-mentioned electrolyte components, one or more additives such as: alkylene carbonate halocarbonates such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glycol dimethyl ether, hexamethylphosphoryltriamine, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted... Zolpidemone, N,N-substituted imidazolidinyl ether, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride.
[0168] According to another exemplary embodiment of the present invention, a battery module comprising the secondary battery as a unit cell and a battery pack comprising the battery module are provided. The battery module and battery pack comprise secondary batteries with high capacity, high rate performance, and cycle performance, and therefore can be used as a power source for medium to large-sized devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and energy storage systems.
[0169] Invention Model
[0170] Preferred embodiments will be presented below to aid in understanding the invention, but these embodiments are provided for illustrative purposes only, and it will be apparent to those skilled in the art that various alternatives and variations are possible within the scope and spirit of the invention, and such alternatives and variations naturally fall within the appended claims.
[0171] Example 1-1
[0172] 100 g of a powder in which Si and SiO2 are mixed in a 1:1 molar ratio is heated in a reactor under vacuum at a sublimation temperature of 1,400 °C. Subsequently, the vaporized Si and SiO2 mixture reacts and condenses into a solid phase in a cooling zone under vacuum at a cooling temperature of 800 °C. Then, pre-silicon-containing particles are prepared by heat treatment at 800 °C in an inert atmosphere. Subsequently, the pre-silicon-containing particles are pulverized for 3 hours using a ball mill after 15 stainless steel ball media are introduced into the pre-silicon-containing particles to obtain particles of a specific size (D). 50 Silicon-containing particles with a diameter of 6 μm were then placed in the hot zone of the CVD equipment while maintaining an inert atmosphere by flowing Ar gas. Methane was then blown into the 900°C hot zone using Ar as a carrier gas and heated for 10 minutes. -1 The reaction was carried out for 20 minutes to form a carbon layer on the surface of the silicon-containing particles.
[0173] Li-doped silicon-containing composite particles were prepared by adding 10g of Li metal powder to 90g of silicon-containing particles and then heat-treating them at 800°C in an inert atmosphere.
[0174] After mixing 1.5 g of Al(PO3)3 with 98.5 g of the silicon-containing composite particles, the resulting mixture was heat-treated at 600 °C to prepare a negative electrode active material in which a surface layer containing Li, Al, P, and O was formed on the surface of the silicon-containing composite particles. The D of this negative electrode active material...50 It has a thickness of 6 μm and a BET specific surface area of 2.5 m². 2 / g.
[0175] During ICP analysis of the negative electrode active material, based on a total of 100 wt% of the negative electrode active material, the contents of Li, Al, and P were 9.5 wt%, 0.15 wt%, and 0.5 wt%, respectively.
[0176] Examples 1-2
[0177] The negative electrode active material was prepared in the same manner as in Examples 1-1, except that AlPO4 was used instead of Al(PO3)3. The negative electrode active material's D... 50 It has a thickness of 6 μm and a BET specific surface area of 2.5 m². 2 / g.
[0178] In the ICP analysis of the negative electrode active material, based on a total of 100 wt% of the negative electrode active material, the contents of Li, Al and P were 9.5 wt%, 0.15 wt% and 0.17 wt%, respectively.
[0179] Examples 1-3
[0180] The negative electrode active material was prepared in the same manner as in Examples 1-1, except that 97g of silicon-containing composite particles and 3g of Al(PO3)3 were used. The D of the negative electrode active material... 50 It has a thickness of 6 μm and a BET specific surface area of 2.5 m². 2 / g.
[0181] During ICP analysis of the negative electrode active material, based on a total of 100 wt% of the negative electrode active material, the contents of Li, Al, and P were 9.4 wt%, 0.3 wt%, and 0.9 wt%, respectively.
[0182] Comparative Example 1-1
[0183] Except for heat treatment at 800°C during surface layer formation, the negative electrode active material was prepared in the same manner as in Examples 1-1. The negative electrode active material's D... 50 It has a thickness of 6 μm and a BET specific surface area of 2.5 m². 2 / g.
[0184] Comparative Examples 1-2
[0185] The negative electrode active material was prepared in the same manner as in Examples 1-1, except that Al(PO3)3 was not mixed with silicon-containing composite particles. The negative electrode active material's D... 50 It has a thickness of 6 μm and a BET specific surface area of 2.5 m².2 / g.
[0186] The negative electrode active materials prepared in the examples and comparative examples are shown in Table 1 below.
[0187] [Table 1]
[0188]
[0189] The contents of Li, Al and P atoms were confirmed by ICP analysis using an inductively coupled plasma atomic emission spectrometer (Perkin-Elmer 7300 ICP-OES AVIO500).
[0190] The phase of the surface layer was identified by the changes in the XRD patterns before and after coating. When the surface layer was amorphous, there was no change in the XRD patterns before and after coating.
[0191] The content of the carbon layer was determined by elemental analysis of combustion (Bruker's G4ICARUS) under oxygen conditions.
[0192] The negative electrode active material D 50 The analysis is performed using a Microtac device via PSD measurement.
[0193] The specific surface area was determined using a BET measuring instrument (BEL-SORP-MAX, Bell Corporation, Japan) by degassing at 200°C for 8 hours and performing N2 adsorption / desorption at 77K.
[0194] <Experimental Example 1: Evaluation of Discharge Capacity, Initial Efficiency, and Capacity Retention>
[0195] Anodes and batteries were prepared using the anode active materials from the examples and comparative examples, respectively.
[0196] A mixture was prepared by mixing the negative electrode active material, carbon black as a conductive material, and polyacrylic acid (PAA) as a binder in a weight ratio of 80:10:10. Subsequently, 7.8 g of distilled water was added to 5 g of the mixture, and the resulting mixture was stirred to prepare a negative electrode slurry. This negative electrode slurry was applied to one surface of a 20 μm thick copper (Cu) metal film serving as the negative electrode current collector and dried. In this case, the temperature of the circulating air was 60 °C. Subsequently, the negative electrode current collector was prepared by rolling it and drying it in a vacuum oven at 130 °C for 12 hours.
[0197] This will be achieved by cutting lithium (Li) metal sheets into 1.7671 cm thick pieces. 2A thin film of lithium (Li) metal obtained by forming a circle is used as the positive electrode. A porous polyethylene membrane is inserted between the positive and negative electrodes. An electrolyte solution containing 0.5 parts by weight of vinylene carbonate dissolved in a mixed solution of ethyl methyl carbonate (EMC) and ethylene carbonate (EC) in a volume ratio of 7:3, and 1M LiPF6 dissolved in the membrane is injected to prepare a lithium coin half-cell.
[0198] The discharge capacity, initial efficiency, and capacity retention of the prepared batteries were evaluated by charging and discharging, and are shown in Table 2 below.
[0199] For the first and second cycles, the battery was charged and discharged at 0.1C, and from the third to the 49th cycle, it was charged and discharged at 0.5C. The 50th cycle ended in a charged state (lithium contained in the negative electrode).
[0200] Charging conditions: CC (constant current) / CV (constant voltage) (5mV / 0.005C current cutoff)
[0201] Discharge conditions: CC (constant current) condition 1.5V
[0202] The discharge capacity (mAh / g) and initial efficiency (%) were derived from the results during the first charge / discharge cycle. Specifically, the initial efficiency (%) was derived through the following calculations.
[0203] Initial efficiency (%) = (discharge capacity after the first discharge / charge capacity after the first charge) × 100. Capacity retention rate is derived from the following calculations.
[0204] Capacity retention rate (%) = (50th discharge capacity / 1st discharge capacity) × 100
[0205] [Table 2]
[0206] Example 1-1 1380 91 40 Examples 1-2 1380 91 40 Examples 1-3 1370 90 40 Comparative Example 1-1 1300 89 35 Comparative Examples 1-2 1250 86 30
[0207] As can be confirmed in Table 2, in Examples 1-1 to 1-3, by providing a surface layer as an amorphous phase on the silicon-containing composite particles, lithium byproducts contained in the silicon-containing composite particles can be effectively removed, and the silicon-containing composite particles are effectively coated by the surface layer, thereby preventing the lithium byproducts and lithium compounds of the silicon-containing composite particles from reacting with the moisture in the slurry and causing the physical properties of the slurry to deteriorate. Therefore, the discharge capacity, initial efficiency and capacity retention are all excellent.
[0208] In contrast, the high heat treatment temperature in Comparative Example 1-1 resulted in the formation of a crystalline material on the surface layer, which made it difficult for Li ions to enter and exit. Therefore, it can be confirmed that the discharge capacity, initial efficiency and lifetime characteristics deteriorated.
[0209] Because Comparative Examples 1-2 did not include a surface layer, the Li compounds contained in the silicon-containing composite particles readily reacted with the moisture in the slurry to change the viscosity of the slurry and caused side reactions in the slurry. Therefore, it can be confirmed that the initial efficiency and lifetime characteristics deteriorated.
[0210] Example 2-1
[0211] Except for dispersing silicon-containing composite particles and Al(PO3)3 in ethanol and then evaporating the ethanol by heating the resulting dispersion at 90°C, a negative electrode active material having a surface layer containing Al, P and O was prepared in the same manner as in Examples 1-1.
[0212] The surface layer of the formed negative electrode active material is amorphous, and based on a total of 100 parts by weight of negative electrode active material, the contents of the surface layer, carbon layer, and Li are 1.5 parts by weight, 4.5 parts by weight, and 9.5 parts by weight, respectively. The D of the negative electrode active material... 50 It has a thickness of 6 μm and a specific surface area of 2.5 m². 2 / g.
[0213] <Experimental Example 2: Evaluation of Rate Capacity Characteristics>
[0214] The negative electrode and battery were manufactured using the negative electrode active materials of Examples 1-1 and 2-1 in the same manner as in Experimental Example 1.
[0215] The charging and discharging of the batteries manufactured in Examples 1-1 and 2-1 were evaluated. While keeping the charging rate constant at 0.2C and changing the discharging rate to 0.2C, 1.0C, 3.0C, and 5.0C, the rate characteristics (rate performance) were measured to observe the degree of decrease in discharge capacity, and are shown in Table 3 below. On the other hand, the discharge capacity at 0.2C was set to 100%.
[0216] [Table 3]
[0217]
[0218] In Examples 1-1 and 2-1, the surface layer is disposed on the surface of the silicon-containing composite particles in the form of an amorphous phase. This effectively prevents the reaction between lithium byproducts and lithium compounds of the silicon-containing composite particles and the moisture in the slurry by coating the silicon-containing composite particles with the surface layer, thereby preventing the deterioration of the physical properties of the slurry.
[0219] In Example 2-1, the surface layer does not contain Li, while the surface layer of Example 1-1 contains Li. Therefore, in Example 1-1, the discharge rate limiting characteristics (rate performance) are excellent due to the reduced Li diffusion resistance on the surface of the negative electrode active material. Thus, it can be confirmed that the discharge capacity of Example 1-1 according to the discharge rate is even better than that of Example 2-1.
Claims
1. A negative electrode active material, said negative electrode active material comprising: SiO x Silicon-containing composite particles of Li compounds, wherein 0 <x<2; A carbon layer on at least a portion of the surface of the silicon-containing composite particles; A surface layer comprising an amorphous phase on at least a portion of the silicon-containing composite particles; and At least one Group 13 element and at least one Group 15 element, wherein The surface layer comprises Li y Al z P w O v an amorphous phase, wherein 0 < y ≤ 10, 0 < z ≤ 10, 0 < w ≤ 10 and 0 < v ≤ 10, and Of the total 100 parts by weight of the surface layer, the content of the amorphous phase contained in the surface layer is greater than 50 parts by weight.
2. The negative electrode active material according to claim 1, wherein no crystallization peak originating from the surface layer appears during X-ray diffraction analysis of the negative electrode active material.
3. The negative electrode active material according to claim 1, wherein, during X-ray diffraction analysis of the negative electrode active material, peaks originating from Si appear, and peaks originating from at least one of Li2SiO3 and Li2Si2O5 appear.
4. The negative electrode active material according to claim 1, wherein the weight ratio of the surface layer to the carbon layer is 1:0.1 to 1:
30.
5. The negative electrode active material according to claim 1, wherein the content of the surface layer is 90 parts by weight or less, based on 100 parts by weight of the carbon layer.
6. The negative electrode active material according to claim 1, wherein the surface layer further comprises one or more selected from the group consisting of Li2O, LiOH and Li2CO3.
7. The negative electrode active material according to claim 1, wherein the Li content is from 0.1 parts by weight to 25 parts by weight based on a total of 100 parts by weight of the negative electrode active material.
8. The negative electrode active material according to claim 1, wherein the carbon layer comprises an amorphous phase.
9. The negative electrode active material according to claim 1, wherein the carbon layer content is from 0.1 parts by weight to 50 parts by weight based on a total of 100 parts by weight of the negative electrode active material.
10. The negative electrode active material according to claim 1, wherein the surface layer exists on at least a portion of the outer surface of the carbon layer.
11. The negative electrode active material according to claim 1, wherein the surface layer exists on a region of the particle surface where the carbon layer is not disposed.
12. A negative electrode comprising the negative electrode active material according to claim 1.
13. A secondary battery comprising a negative electrode according to claim 12.
Citation Information
Patent Citations
Method for fabricating carbon-coated silicon / graphite composite anode material for lithium secondary battery and method for fabricating secondary battery comprising the same
KR100794192B1
Resistance reduction for word lines in memory arrays
KR1020210107524A
Gas mixture for Ion Implantation.
KR1020220055522A
Negative electrode active material for battery, preparation method of negative electrode active material, battery negative electrode and battery
CN112018367A
Negative electrode active material for non-aqueous electrolyte secondary battery, non-aqueous electrolyte secondary battery, and method of producing negative electrode material for non-aqueous electrolyte secondary battery
US20180175377A1